Deep Learning Based Deforestation and Classification (International Journal of Scientific Research in Science and Technology, 2025)
Cervical cancer remains a significant global health concern, consistently ranking among the top four causes of cancer-related deaths in women. The chances of survival can be greatly improved through the early identification of cervical intraepithelial neoplasia (CIN).a precursor to cervical cancer, is crucial for improving patient outcomes. This study presents a deep learning-based approach for the accurate classification of cervical cancer status as either positive or negative. Leveraging the capabilities of Convolutional Neural Networks (CNNs) and transfer learning, we employ the ResNet50 architecture to analyze cervical cell images. A dataset comprising images sourced from various internet repositories, supplemented with augmented samples to enhance diversity, was utilized for training and evaluation. The CNN model demonstrated high accuracy in distinguishing between malignant and benign cases, underscoring its potential as a reliable diagnostic tool. By automating the detection process, this approach aims to assist healthcare professionals in early diagnosis, thereby facilitating timely intervention and treatment. The integration of deep learning techniques in medical diagnostics holds promise for enhancing the efficiency and accuracy of cervical cancer screening programs.